Dynamics of the Arctic Fox Population on St. Lawrence Island, Bering Sea - Fay, Francis H.; Rausch, Robert L. (DigitalCommons@University of Nebraska - Lincoln, 1992)
English abstract: We hypothesized that the arctic fox, Alopex lagopus (Linnaeus), population on St. Lawrence Island was cyclic and that its fluctuations in size. structure, and productivity were correlated with the relative size of the population of northern voles, Microtus oeconomus Pallas, the primary prey. Based on a nine-year study, we determined that the variations in size of the fox and vole populations were similar, but they both were of low amplitude and not closely correlated. The high pregnancy rate (mean, 86%/yr) and numbers of young conceived (mean, 11.5/pregnancy) did not vary significantly among years, probably because of the consistently abundant and diverse food supply available to the foxes. The age composition of the trappers' catch of foxes each winter also was comparatively stable, but it was closely correlated with the size of the vole population in the previous summer. The survival of the young foxes during the summer probably was dependent on the availability of the voles, The composition of the catch also appeared to be influenced by immigration of faxes from the adjacent continents via the pack ice. French abstract: Nous avons émis I'hypothèse que la population du renard arctique, Alopex lagopus (Linnaeus), sur I'île Saint Lawrence était cyclique el que les fluctuations concernant sa tailIe, sa structure et sa productivité étaient corrélées à la taille relative de la population du campagnol nordique. Microtus oeconomus Pallas, sa principale proie. En nous appuyant sur une étude menée sur neuf ans, nous avons déterminé que les variations dans la taille des populations du renard et du campagnol étaient semblables. mais que toutes deux avaient une faible amplitude et n'étaient pas corrélées de façon étroite. Le taux de grossesse élevé (moyenne 86 p. cent/an) et Ie nombre dc petits conçus (moyenne 11,5/grossesse) ne variaient pas de façon significative au cours des ans, probablement à cause de I'abondance et de la variété de sources de nourriture pour les renards. La composition d'âge des ...